The Brexit Referendum on Twitter : a mixed-method, computational analysis - Tong, Jingrong; Zuo, Landong (Emerald Publishing Limited, 2021)
This book explores Twitter communication about the 2016 Brexit referendum in the UK in the run-up to the event. The mixed-method, computational analysis of over twelve million tweets reveals how Twitter worked in shaping political discourse and its potential for fuelling populism in the month leading to the referendum. Our findings show while polarised public opinion was explicitly expressed, populist sentiments were mainstreamed into the debate about the referendum and widely spread on Twitter. Populist politicians, supported by pro-Brexit users, tactically used Twitter to promulgate their populist ideas. In contrast, despite their active use of Twitter, the Remain camp appeared to have misunderstood the mechanisms of Twitter for shaping political discourse. Twitter communication, in this case, showed dangerous potential for reflecting and reinforcing existing social tensions and divisions, being influenced or even manipulated by individuals and interest groups to serve their own interests. It is important to be well aware of this capacity of Twitter for the wellbeing of democracy, especially in the politically turbulent times since 2016 when the UK voted to leave the EU.
Includes index.
Keywords: European Union -- Great Britain -- Social aspects.; Social media -- Influence.; Social media -- Political aspects -- Great Britain.; Twitter (Firm) -- Influence.; Social Science -- Media Studies.; Political ideologies.; elektronické knihy; electronic books